A bifunctional robust metal sulfide with highly selective capture of Pb2+ ions and luminescence sensing ability for heavy metals in aqueous media. Issue 17 (4th August 2021) - Pournara, Anastasia D.; Bika, Christina-Georgia; Chen, Xitong; Lazarides, Theodore; Kaziannis, Spyridon; Feng, Pingyun; Manos, Manolis J.
Abstract : A 3-D metal sulfide ion exchanger (MSIE) with extra-framework H + ions showed a remarkable capability for sorption of Pb 2+ ions and highly efficient luminescence sensing properties towards various heavy metal ions. Abstract : Heavy metal ions represent hazardous and harmful contaminants for living organisms and the environment and thus, it is of urgent need to develop new materials sufficient to detect and remove them efficiently. Herein, we report the metal sulfide ion exchanger (MSIE) H x Ga x Ge4− x S8 · y H2 O (protonated UCR-20, p-UCR-20 ) which demonstrates exceptional capability for both detection and removal of heavy metals from aqueous samples. This material exhibited exceptional fast sorption kinetics (≤1 min), high sorption capacity (∼527 mg g −1 ) and remarkable selectivity for Pb 2+ towards various common alkali and alkaline earth cations and in highly acidic to alkaline conditions. Even more importantly, p-UCR-20 in its composite form with calcium alginate was used as stationary phase (along with silica sand) in a fixed-bed ion exchange column and was found capable of eliminating traces of Pb 2+ from a large volume of a wastewater simulant solution. Photophysical studies revealed that p-UCR-20 shows excellent luminescence sensing properties for Pb 2+, achieving limits of detection below the acceptable Pb levels in water and such efficient sensing properties are largely retained even in the presence of several antagonistic species in large excess. In addition, p-UCR-20 displays highly efficient sensing properties for additional heavy metal ions, such as Ni 2+ and Cd 2+ . Overall, the results derived from the current study reveal for the first time that MSIES may be a source not only of excellent sorbents but also exceptional luminescent sensors for heavy metal ions in aqueous media.